How dear to my heart - Kimbrough, Emily frey50; Hokinson, Helen E. (Bloomington, IN Indiana University Press, 1991)
This book is the authors recollections, with laughter and merriment, fo what life was like in a small American town in the first decade of this century.
Keywords: Kimbrough, Emily, -- 1899- -- Childhood and youth; Authors, American -- 20th century; Muncie (Ind.) -- Social life and customs; Indiana